Ennead V.1: on the three primary levels of reality - Plotinus; Perl, Eric David (The Enneads of Plotinus with philosophical commentaries, 2015)
Title Page ; Copyright Page ; Contents; Dedication; Introduction to the Series; Abbreviations; Acknowledgments; Introduction to the Treatise; Note on the Text; Synopsis; Translation of Plotinus Ennead V.1; Commentary; Chapter 1; Chapter 2; Chapter 3; Chapter 4; Chapter 5; Chapter 6; Chapter 7; Chapter 8; Chapter 9; Chapter 10; Chapter 11; Chapter 12; Select Bibliography; Index of Ancient Authors; Index of Names and Subjects; Also Available From Parmenides Publishing